Winning over the sceptics: how end-consumers view the motives and authenticity of customer-entrepreneurs over time - Tourky, Marwa; Ebeid, Maha; Shaalan, Ahmed; Agag, Gomaa (Elsevier, 2026)
Customer-entrepreneurs are an emerging sales force in online retailing, combining the traditional roles of customers and entrepreneurs by using digital platforms to advertise and sell products. A handful of researchers have begun exploring the phenomenon from different perspectives. We build on this emergent literature stream by investigating the perspective of end-consumers. Integrating attribution theory and the elaboration likelihood model, we develop a conceptual model and hypotheses to explore the pathways between end-consumers’ perceptions of the motives and authenticity of customer-entrepreneurs, the mediating role of consumer scepticism in this relationship and the outcomes for three customer mindset metrics (customer satisfaction, loyalty intention and perceived service quality) and resilience to negative information. Finally, we measure the moderating effect of consumers’ previous experience with a customer-entrepreneur on the relationship between perceived motives and scepticism. Our time-lapse study uses structural equation modelling and longitudinal analysis of data gathered from 539 consumers in the first wave of data collection and 476 consumers in the second wave. The findings indicate that perceived intrinsic motives support perceived authenticity, perceived extrinsic motives fuel scepticism, and scepticism partially mediates the link between perceived motives and perceived authenticity. Moreover, we find that perceived authenticity significantly impacts all four studied outcomes, and that previous experience moderates the relationship between perceived intrinsic motives and scepticism. Our findings guide customer-entrepreneurs, managers, and policymakers in harnessing this new phenomenon effectively.
Keywords: 3503 Business Systems In Context; 3504 Commercial Services; 3506 Marketing; Marketing; 35 Commerce, management, tourism and services; Customer-entrepreneurs; Customer mindset metrics; Entrepreneur authenticity; Perceived motives; Resilience to negative information; Scepticism